The unusual stability of H-bonded complexes in solvent caused by greater solvation energy of complex compared to those of isolated fragments - Lo, Rabindranath; Mašínová, Anna; Lamanec, Maximilián; Nachtigallová, Dana; Hobza, Pavel (Journal of computational chemistry, 2023)
Here, the effect of solvent on the stability of non-covalent complexes, was studied. These complexes were from previously published S22, S66, and X40 datasets, which include hydrogen-, halogen- and dispersion-bonded complexes. It was shown that the charge transfer in the complex determines whether the complex is stabilized or destabilized in solvent.
Keywords: termodynamika; fyzikální jevy; Solvents; Hydrogen Bonding; binding energies; vodíková vazba; charge transfer; hydrogen-bonded complexes; dispersion-bonded complexes; rozpouštědla; Halogens; halogeny; halogen-bonded complexes; Physical Phenomena; Thermodynamics